Self-assembled metallic nanoparticle template — a new approach of surface nanostructuring at nanometer scale - Taleb, A.; Ivanova, V. (Condensed Matter Physics, 2017)
In the present work, the formation of silver and copper nanostructures on highly oriented pyrolytic graphite
(HOPG) modified with self-assembled gold nanoparticles (Au NPs) is demonstrated. Surface patterning with
nanometer resolution was achieved. Different methods such as field emission scanning electron microscopy
(FEGSEM), energy dispersive spectrometry (EDS) and X-ray photoelectron spectroscopy (XPS) were used to illustrate a selective deposition of silver and copper on Au NPs. The mechanism of silver and copper ions reduction
on Au NP with n-dodecanethiol coating is discussed. В данiй роботi продемонстровано наноструктури срiбла i мiдi на високо орiєнтованому пiролiтичному графiтi (HOPG), модифiкованому самозгромадженими золотими наночастинками (Au NPs). Отримано
формування рисунку на поверхнi з нанометровою роздiльною здатнiстю. Рiзнi методи, такi як автоелектронний скануючий мiкроскоп (FEGSEM), енергетично розсiювальний спектрометр (EDS) i X-променева
фотоелектронна спектроскопiя, були використанi для того, щоб проiлюструвати селективне осадження срiбла i мiдi на Au NP. Обговорено механiзм меншання iонiв срiбла i мiдi на Au NP з покриттям nдодеканетiолом.